2021
DOI: 10.1002/ppul.25775
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic evaluation of inhaled nitric oxide use among neonates with gestational age less than 35 weeks

Abstract: Background and Objectives The use of inhaled nitric oxide (iNO) in +late preterm and term infants with pulmonary hypertension is Food and Drug Administration (FDA) approved and has improved outcomes and survival. iNO use is not FDA approved for preterm infants and previous studies show no mortality benefit. The objectives were 1) to determine the usage of iNO among preterm neonates <35 weeks before and after the 2010 National Institutes of Health consensus statement and 2) to evaluate characteristics and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In our study, the median maximum dose for iNO was observed to be 20 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) among positive responders, compared to 40 in negative responders. Inhaled nitric oxide has a good safety profile used at 20ppm, while lower doses may be equally as effective as higher doses.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In our study, the median maximum dose for iNO was observed to be 20 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) among positive responders, compared to 40 in negative responders. Inhaled nitric oxide has a good safety profile used at 20ppm, while lower doses may be equally as effective as higher doses.…”
Section: Discussionmentioning
confidence: 61%
“…As literature on PHT primarily centres on preterm infants with moderate or severe BPD, data on EOPAH and HRF is scarce. Despite significant evidence demonstrating that iNO has no effect on reducing the morbidity or mortality of extremely premature neonates, the offlabel prescription of iNO is increasing (30,31). On the other hand, evidence suggests that iNO can be beneficial for a selected subpopulation of extremely premature neonates (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of preterm infants with iNO use in the United States during 2004-2016 were those with a gestational age of < 27 weeks, and the use of iNO among infants with a gestational age of ≤ 24 weeks increased from 19.8-22.7% during 2011-2016 compared with 2004-2010. [9] The Canadian Neonatal Collaborative Network reported in 2015 that The proportion of neonates who received iNO in the 22-25, 26-29, and 30-33 weeks' GA groups was 16.1, 6.0, and 1.3%, respectively [20]. Our results showed that the younger the gestational age, the lower the number of people who had used it; only approximately 26.2% (68/260) used iNO in infants with a gestational age of < 28 weeks, and gestational ages < 34 and < 28 weeks were considered contraindications for iNO by 23% and 53% of the investigators, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in the United States in 2010 reported a 6-fold increase in iNO use between 2000 and 2008 in infants with less than 34 weeks gestation, and the largest increase was observed among infants with 23-26 weeks gestation [8]. There was also a signi cant increase in the use of iNO in preterm infants in the United States between 2011 and 2016 [9]. Moreover, a survey also showed increasing use of iNO in preterm infants admitted to neonatal units in the United Kingdom between 2010 and 2015 [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, because iNO treatment might produce major adverse events such as oxidative stress damage and bleeding, the National Institutes of Health does not recommend it in premature infants [ 9 ]. Peluso et al conducted a population-based cross-sectional research on premature infants at gestational age less than 35 weeks and found that iNO use increased from 2011 to 2016 compared to 2004 to 2010 [ 10 ]. Currently, there are disagreements regarding patient selection, age of inclusion, initial and maximum dose, course of treatment and efficacy on the usage of iNO.…”
Section: Introductionmentioning
confidence: 99%